Soil Seed Bank Characteristics of Nitraria tangutorum Nebkhas in a Desert–Oasis Ecotone - Li, Min; Xiao, Huijie; Xin, Zhiming; Li, Xing; Li, Junran; Miri, Abbas; Cao, Qiqi (Frontiers in Environmental Science, 2022)
Understanding soil seed banks (SSBs) of Nitrariatangutorum nebkhas is critical for vegetation restoration and ecological management in desert–oasis ecotones. In this study, we conducted a survey in the field and a seed germination experiment in the laboratory to investigate the characteristics of SSB in different sizes and parts of nebkhas and to examine their relationship with aboveground vegetation. The results showed that there were 17 species of plants in six families in the SSB of Nitraria tangutorum nebkhas in a desert–oasis ecotone, dominated by Chenopodiaceae. The life forms were mainly annual herbs, accounting for 58.82%–71.43%. The number of species in the SSB were in the order of large nebkha > medium nebkha > small nebkha, and there was no significant difference in SSB density. However, SSB densities in different parts of each nebkha were in the order bottom > middle > top. The densities were significantly different and showed a decreasing trend as soil depth increased. Most of the plant seeds were distributed in the 0–5 cm soil layer. The similarity coefficient between the SSB of each nebkha and the aboveground vegetation was high. From the bottom to the top, the number of common species and similarity coefficient between the aboveground vegetation and the SSB decreased, and the number of species in the SSB was greater than that of the aboveground vegetation. Vegetation plays a decisive role in the initial development of a nebkha. When the nebkha develops to a certain extent, it reacts to the vegetation, thereby intensifying the differences in the composition of vegetation species in different parts of the nebkha and further affecting the SSB.